Keputusan Santri Dalam Membeli Di Online Shop: Antara Lifestyle, Trust Dan Price - Umma, Eri Shofa Rohmatul; Qomar, Moh. Nurul; Arifin, Jaenal (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
This study aims to determine the influence of Lifestyle Trust and Prices on Purchasing Decisions in Onlineshop at Raudlatul Falah Islamic Boarding School Students in Pati Patis. This type of research is quantitative, with a total sample of 81 respondents. Data analysis techniques include validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination, and t- test. The results of this study indicate that lifestyle and trust have a positive and significant effect, while price does not significantly influence purchasing decisions online at Raudlatul Falah boarding school students in Gembong Pati. With a lifestyle significance test of 0, 000 with a t- count of 6. 374, a significance level of confidence of 0. 002 with a t- count of 2. 350, and a price significance level of- 0. 786 with t- count of- 0. 273. It can be concluded that H1 and H2 in this study were accepted and H3 was rejected.